New Approaches in Vital Pulp Therapy in Permanent Teeth - Ghoddusi, Jamileh (Iranian Center for Endodontic Research, 2014)
Vitality of dental pulp is essential for long-term tooth survival. The aim of vital pulp therapy is to maintain healthy pulp tissue by eliminating bacteria from the dentin-pulp complex. There are several different treatment options for vital pulp therapy in extensively decayed or traumatized teeth. Pulp capping or pulpotomy procedures rely upon an accurate assessment of the pulp status, and careful management of the remaining pulp tissue. The purpose of this review is to provide an overview of new approaches in vital pulp therapy in permanent teeth.